Acenequinocumulenes: Lateral and vertical π-extended analogs of tetracyanoquinodimethane (TCNQ) - Gruber, Marco; Padberg, Kevin; Min, Jie; Waterloo, Andreas; Hampel, Frank; Maid, Harald; Ameri, Tayebeh; Brabec, Christoph; Tykwinski, Rik (Chemistry - A European Journal, 2017)
We have designed a series of molecules and developed synthetic methodology that allows for the inclusion of structural diversity along both the lateral and vertical axes of the basic TCNQ skeleton. In the lateral direction, benzoannulation extends the π-system through (hetero)acene formation, while incorporation of a [3]cumulene increases delocalization vertically. The potential of these new molecules as semiconductors is explored through UV-vis spectroscopy, cyclic voltammetry, X-ray crystallography, thin film formation, and mobility measurements (via space charge limited current measurements
Keywords: pentacenes; donor-acceptor; organic materials; cumulenes; synthetic methodology

Bridged triarylboranes, -silanes, -amines, and -phosphines as minimalistic heteroatom-containing polycyclic aromatic hydrocarbons: Progress and challenges - Schaub, Tobias A.; Padberg, Kevin; Kivala, Milan (Journal of Physical Organic Chemistry, 2019)
Minimalistic heteroaromatic scaffolds result from the introduction of various ortho-bridging moieties into triarylboranes, -silanes, -amines, and -phosphines. This molecular design opens an avenue to a class of structures fascinating not only from a fundamental standpoint, but also because of their aptitude to serve as active materials in organic electronics. In this Review, the history of these conceptually simple heteroatom-containing π-systems is briefly summarized, and the current state-of-the-art in this vividly expanding field of research is discussed. The synthetic strategies towards these scaffolds are covered together with their structural and electronic traits. Special focus is dedicated to the recent progress and challenges in the molecular design of functional materials made thereof.
CRIS-Team Scopus Importer:2019-12-03
Keywords: bowl-shaped scaffolds; heteroatom-containing π-systems; heterotriangulenes; planarized π-systems; polycyclic aromatic hydrocarbons

Double bonds? Studies on the barrier to rotation about the cumulenic C=C bonds of tetraaryl[n]cumulenes (n=3,5,7,9) - Bühringer, Martina; Padberg, Kevin; Phleps, Daniel; Maid, Harald; Placht, Christian; Neiß, Christian; Ferguson, Michael J.; Görling, Andreas; Tykwinski, Rik (Angewandte Chemie International Edition, 2018)

Isomeric Dithienophosphepines: The Impact of Ring Fusion on Electronic and Structural Properties - Padberg, Kevin; Ascherl, Johannes D. R.; Hampel, Frank; Kivala, Milan (Chemistry - A European Journal, 2020)
The synthesis and extensive experimental (X-ray crystallography, UV/Vis spectroscopy, cyclic voltammetry) and theoretical (DFT calculations) characterization of two isomeric dithieno[b,f]phosphepines (DTPs) are presented herein. The relative orientation of the phosphepine and the thiophene moieties has a decisive impact on the electronic and structural properties of these compounds. Moreover, the thiophene units allow for a facile subsequent functionalization through direct Pd-catalyzed C-H coupling, which renders DTPs highly promising building blocks for organophosphorus functional materials.
CRIS-Team WoS Importer:2020-02-11

The renaissance of bridged triarylphosphines: Towards organophosphorus molecular bowls - Schaub, Tobias A.; Padberg, Kevin; Kivala, Milan (Chemistry Letters, 2019)
Bridged triarylphosphines represent conceptually simple members of an emerging class of polycyclic aromatic hydrocarbons with embedded phosphorus atoms. Their auspicious attributes have spurred a renewed scientific interest in these fascinating molecular bowls after having fallen into oblivion for more than two decades. In this Highlight Review historical aspects of fully bridged triarylphosphines are discussed and recent advances in this research field are summarized with a focus on the challenges that lie ahead.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Organophosphorus materials; Phosphorus heterocycles; Polycyclic aromatic hydrocarbons